2010
DOI: 10.1007/s10668-010-9278-0
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and variability in Sub-Saharan Africa: a review of current and future trends and impacts on agriculture and food security

Abstract: Sub-Saharan Africa has been portrayed as the most vulnerable region to the impacts of global climate change because of its reliance on agriculture which is highly sensitive to weather and climate variables such as temperature, precipitation, and light and extreme events and low capacity for adaptation. This article reviews evidence on the scope and nature of the climate change challenge; and assesses the impact of climate change on agriculture and food security in Sub-Saharan Africa. From the review, it is app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
248
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 451 publications
(286 citation statements)
references
References 56 publications
6
248
1
2
Order By: Relevance
“…In sub-Saharan Africa, such research has suggested that overall, East Africa will experience wetter weather and Southeast Africa will become drier (Kotir 2011). Changes in rainfall patterns are expected to result in loss of cropland (Niang et al 2014;Kotir 2011). Crop yields in most of sub-Saharan Africa are estimated to fall by at least 10-20 % by 2050 (Kotir 2011;Thornton et al 2011).…”
Section: Climate Change Impacts Vulnerability and Adaptation (Iva)mentioning
confidence: 99%
See 2 more Smart Citations
“…In sub-Saharan Africa, such research has suggested that overall, East Africa will experience wetter weather and Southeast Africa will become drier (Kotir 2011). Changes in rainfall patterns are expected to result in loss of cropland (Niang et al 2014;Kotir 2011). Crop yields in most of sub-Saharan Africa are estimated to fall by at least 10-20 % by 2050 (Kotir 2011;Thornton et al 2011).…”
Section: Climate Change Impacts Vulnerability and Adaptation (Iva)mentioning
confidence: 99%
“…Changes in rainfall patterns are expected to result in loss of cropland (Niang et al 2014;Kotir 2011). Crop yields in most of sub-Saharan Africa are estimated to fall by at least 10-20 % by 2050 (Kotir 2011;Thornton et al 2011). Arid and semiarid regions of the continent are expected to expand (Kotir 2011).…”
Section: Climate Change Impacts Vulnerability and Adaptation (Iva)mentioning
confidence: 99%
See 1 more Smart Citation
“…Wheat is a C3 crop that is sensitive to drought stress and high temperature conditions, especially during the post-anthesis growth stages, when the crop is often faced by erratic rainfall and prolonged dry spells (Alain et al, 2011;Ilker et al, 2011). Breeding wheat cultivars with drought and heat tolerance is considered to be an economic and sustainable drought mitigation strategy, notably under low input farming systems in sub-Saharan Africa (Kotir, 2011). Suitable genetic resources with complementary drought adaptive traits are required to speedup breeding of wheat cultivars that are better adapted to marginal rainfall conditions (Manes et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Increased incidence of extreme storms and floods are also projected [3]. Sub-Saharan Africa (SSA) is anticipated to experience both seasonal and annual rainfall variability [4,5]. Rising temperatures in combination with increased rainfall variability can adversely affect land-based livelihood systems that (ii) What is the extent of policy coherence amongst the climate-sensitive sector policies of Ghana's economy?…”
Section: Introductionmentioning
confidence: 99%